Instrument development and contextualization for perceived characteristics of e-transactions. Issue 1 (3rd April 2017) - Abunadi, Ibrahim; Alqahtani, Fayez
Abstract : Purpose: The purpose of this paper is to identify and develop a contextualized model and instrument to assess citizens' transactions with government organizations, with a view to predicting and elucidating acceptance of e-transactions. For this purpose, a research model (perceived characteristics of e-transactions acceptance) is developed. Design/methodology/approach: In order to analyze e-transaction acceptance and identify the requirements of the research context, several models were considered. An approach was employed to contextualize or localize the theoretical model, questionnaire items, and the instrument. An online survey gathered the responses of 663 Saudi citizens. Findings: Exploratory and confirmatory factor analyses showed that the measurement model was the most suitable for the collected data. In addition to developing a conceptual research model and instrument, the present study provides a rigorous methodology for contextualizing the model, questionnaire items, and the instrument. Originality/value: This paper develops an original instrument derived from rigorous information systems methodology research. The research model could also be utilized in emerging economies that are implementing e-government to improve the development of e-government services and facilitate acceptance of electronic government transactions, ultimately enhancing citizens' lives.